Categorization of the sumptom thoracic pain type isquemic in the woman to the light the theory of unpleasant symptoms (2010)
Coronary heart disease is the first cause of mortality among Colombia's female population (1) and constitutes a health problem that implies deterioration of the quality of life of this group. The objective of this study was to categorize the ischemic thoracic pain in women in light of the theory Of Unpleasant Symptoms. The study was designed to be descriptiveexploratory with a qualitativequantitative approach. The information was collected by means of a semistructured interview and samples as gathered with information supplied by 30 women who were diagnosed with unstable heart pain or acute heart attack at San Rafael Hospital and at San Sebastián Clinic in Giradot from July to November 2005. The results showed women between 50 and 95 years of age, the majority classified to be within a low social class and level of education. As to the physiological factor, the most representative pathologic background from cardiovascular origin was high blood pressure, followed by diabetes. Within the psychological factors, the most representative category in frequency was "what women believe and know about the symptoms and the disease" and in the situational factors "heat affects me". In terms of the quality dimension, the outstanding category was "major commitment with being a human being". The symptom was referred to a severe intensity in 93% of the cases, and the average grade was 9,48 in a visual analogue scale. Within the consequences of the symptom, the most representative was "Controlling physical activity". The most frequent secondary symptoms were "vomit", "dizziness" and "headache". A symptomatic profile is observed, which is expressed with a linguistic richness and that shows concatenation processes within her health experience that enables us to understand her situation better and consequently to provide adequate care.